2016
DOI: 10.1002/hep.28372
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the cyclin‐dependent kinase inhibitor p57 is mediated by Jab1/Csn5 in hepatocarcinogenesis

Abstract: Down-regulation of p57 (KIP2) cyclin-dependent kinase inhibitors accelerates the growth and invasion of hepatocellular carcinoma (HCC), suggesting that p57 may play an important role in liver carcinogenesis. However, the mechanism or oncogenic signal leading to p57 down-regulation in HCC remains to be determined. Herein, we demonstrated that Jab1/Csn5 expression is negatively correlated with p57 levels in HCC tissues. Kaplan-Meier analysis of tumor samples revealed that high Jab1/Csn5 expression with concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…An increasing number of studies have shown that the expression of CIP/KIP family members is associated with anticancer treatment . Our previous studies suggested that p57 is expressed at a lower level in HCC tissues than in adjacent mucosae, and that decreased p57 levels are a predictor of poor outcomes in HCC patients . Additionally, our results revealed that the up‐regulation of p57 could improve the antitumour effects of cisplatin treatment in HCC cells .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…An increasing number of studies have shown that the expression of CIP/KIP family members is associated with anticancer treatment . Our previous studies suggested that p57 is expressed at a lower level in HCC tissues than in adjacent mucosae, and that decreased p57 levels are a predictor of poor outcomes in HCC patients . Additionally, our results revealed that the up‐regulation of p57 could improve the antitumour effects of cisplatin treatment in HCC cells .…”
Section: Introductionsupporting
confidence: 56%
“…It has been suggested that p57 is a tumour suppressor gene and plays vital roles in the proliferation and migration of tumour cells. Our previous studies have revealed that p57 downregulation results in accelerated growth in HCC cell lines by upregulating the levels of cyclin D1 and CDK2 and enhancing the activities of the CDK4/cyclin D1 and CDK2/cyclin E complexes. Furthermore, by transferring LIMK1 from the cytoplasm to the nucleus, p57 changes the level of phosphorylation of cofilin, thereby regulating HCC invasion and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…We determined the expressions of miR‐155‐5p and PTEN mRNA in a rat model of HCC induced by diethylnitrosamine/N‐nitrosomorpholine (DEN), which is similar to human HCC in terms of morphology and histology . The tumor types of all specimens were confirmed by two independent pathologists . Real‐time PCR results showed that miR‐155‐5p was significantly upregulated in 19 HCC tissues, but PTEN mRNA was downregulated in 14 HCC tissues from chemically‐induced HCC rats, compared with normal rats ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Eight‐week‐old male Sprague–Dawley rats were purchased from the Shanghai Experimental Animal Center and were housed in a pathogen‐free facility at the Animal Center of Xi'an Jiaotong University and the establishment of a rat model of chemically induced HCC was performed as previously described. The tumor types of all specimens were confirmed by two independent pathologists …”
Section: Methodsmentioning
confidence: 99%
“…Tumor sphere numbers and volumes were estimated under a phase microscope at ×40 magnification every 3 days. ppm) containing water for 20 weeks (Guo et al, 2016). Saline was administered in control group rats (n = 15).…”
mentioning
confidence: 99%